The Politics of Religious Heritage: Framing Claims to Religion as Culture in Spain - Astor, Avi (Journal for the scientific study of religion, 2017)
This article contributes to sociological theorizations of religion as heritage through analyzing the politics of religious heritage in Spain since its transition to democracy during the late 1970s. Our analysis is organized around three historical sequences of critical importance for understanding the political and legal significance of discourses that frame religion as cultural heritage in Spain: (1) negotiations that took place during Spain's democratic transition between 1977 and 1980; (2) discussions that surfaced in the context of the state's decision to recognize Islam, Protestantism, and Judaism in 1992; and (3) more recent debates regarding the incorporation of religious minorities in the context of increasing religious diversity, especially concerning places of worship. We show how framing religion using the language of cultural heritage has provided religious actors with a means of defending the connection between religion and national identityand of protecting the privileges of majoritarian religious institutions without violating core tenets of secularism or pluralism. This scenario has created space for certain religious minorities to claim a place within Spain's evolving socioreligious landscape by invoking alternative heritages from Spain's multicultural past.